Kedudukan Gratifikasi Seksual dalam KUHP Nasional: Studi Komparatif Hukum Pidana Indonesia dan Singapura - Sabrina Gita Salsabella; Nadea Lathifah Nugraheni; Praditya Arcy Pratama (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Sexual gratification enforcement in Indonesia faces legal ambiguity. This study examines its position in Indonesian criminal law through a comparative study with Singapore. Using normative methods and a socio-legal approach, findings show that Indonesia's